Maturity and school outcomes in an inflexible system: Evidence from Catalonia - Caterina Calsamiglia; Annalisa Loviglio (SERIEs - Journal of the Spanish Economic Association, 2020)
The existence of a rigid cutoff date which determines when children start primary school creates a large heterogeneity in students' level of maturity within the classroom. We use rich administrative data of the universe of public schools in Catalonia to show that: (1) relatively younger children do significantly worse both in tests administered at the school level and at the regional level, and they experience greater retention. (2) These effects are homogeneous across SES and significant across the whole distribution of performance. (3) Younger children in our data exhibit higher dropout rates and choose the academic track in secondary school less often. (4) Younger children are more frequently diagnosed with learning disorders.
Keywords: I21; I28; H75; 330; Human capital; Entry age; School cutoff date